(untitled) (Al-Qamar, 2021)
The study is exploratory in nature in the interpretivist paradigm. It is based upon Critical Discourse Analysis of Stanley Wolpert’s book “Shameful Flight”. The study is qualitative with special focus on ideological construction of Gandhi and Jinnah by Wolpert. Six events have been specially focused: introduction, Cripps Mission, Satyagrah Movement, Wavell Plan, Shimla conference and Direct Action by Muslim League. Fairclough’s model has been used for discourse analysis of the selected textual items. In these sections of the book contrastive pictures of Gandhi and Jinnah have been given. Main purpose of study has been the explication of Orientalist ideology behind contrastive pictures of both the leaders. Jinnah being the leader of a minority is suppressed, rather ridiculed explicitly; while Gandhi being the nationalist is implicitly defended. The cause behind implicit defense of Gandhi on the one hand is to ridicule Muslims’ ideological stance, and on the other hand is to uphold American’s own ideological stance on partition. The purpose of the study is to foreground American’s implicit ideology about partition of subcontinent and to raise awareness about the discursive injustice to the ideology of Pakistan. The secular aspect of Jinnah’s personality is ideologically highlighted to prove Islamic ideology as hollow and abstract